WEB-BASED FINANCIAL MANAGEMENT INFORMATION SYSTEM FOR MSMES USING RAD METHOD - Haikal Rizky; Vany Terisia; Muhajir Syamsu (Journal of Computer Science Advancements, 2025)
Micro, Small, and Medium Enterprises (MSMEs), such as the Sukamurni Cracker Factory, often rely on manual financial recording, a practice prone to human error, data loss, and significant inefficiencies in generating financial reports. This research addresses these challenges by developing a web-based financial management information system tailored to the operational needs of MSMEs. The primary objective was to design and implement a system that improves the effectiveness, efficiency, and accuracy of financial record-keeping. The study employed the Rapid Application Development (RAD) methodology, encompassing requirements planning, user design, rapid construction, and system validation. The resulting system was built using the Laravel framework, PHP programming language, and a MySQL database. Functional validation was conducted through Black Box testing, which confirmed that all system modules—including income and expense tracking, automated report generation, and role-based access control for Admins and Staff—operate as specified. The novelty of this work lies in its practical application of the RAD model to create a user-centric and rapidly deployable solution for a resource-constrained MSME environment. This research provides a functional model for digital transformation in small-scale businesses, demonstrating that a well-designed system can significantly enhance operational efficiency and support strategic decision-making.